2021
DOI: 10.1093/eurheartj/suab100
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy and COVID-19

Abstract: SARS-CoV-2 infection is associated with frequent thrombotic events, at the micro and macro-vascular level, due to the perpetuation of a state of hypercoagulability. The so-called ‘COVID-19 associated coagulopathy’ (CAC) represents a key aspect in the genesis of organ damage from SARS-CoV-2. The main coagulative alterations described in the literature are represented by high levels of D-dimer and fibrinogen. Although CAC has some common features with disseminated intravascular coagulation and sepsis-induced coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 66%
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 66%
“…Following SARS-CoV-2 infection, as with all infections, the human body, to defend itself, naturally triggers the innate immune system, although excessive immune responses can lead to inflammatory storms with injury to the microcirculation and activation of the coagulation system with the development of disseminated intravascular coagulation [ 6 ]. A state of hypercoagulability has been identified in cases of COVID-19, being a key aspect of micro- and macro- vascular thrombosis found in patients with this infectious disease [ 7 , 8 ]. Abnormalities of blood coagulation parameters were reported, particularly in patients with COVID-19 associated pneumonia and ARDS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In critically ill patients, these monocytic cells activate excessive inflammation in response to sensing PAMPs and DAMPs, which may further be exacerbated by the reduction in monocyte-originated macrophages whose role is to phagocytose the ensuing debris ( 134 , 154 , 155 ). An additional signal to trigger hyperinflammation underlying severe illness is the release of neutrophil extracellular traps (NET) and NET-stimulated coagulopathy ( 156 ). NETosis is likely initiated by both direct (through angiotensin-converting enzyme 2, serine protease, virus replication, and PAD-4 ( 157 )) and indirect (through activated platelets and COVID-19-triggered cytokines and chemokines which stimulate NETosis ( 158 )) mechanisms.…”
Section: Implications For Covid-19mentioning
confidence: 99%